Translating LPOD and CR-Prolog2 into standard answer set programs. Issue 3 (10th August 2018) - LEE, JOOHYUNG; YANG, ZHUN
Abstract: Logic Programs with Ordered Disjunction (LPOD) is an extension of standard answer set programs to handle preference using the construct of ordered disjunction, and CR-Prolog2 is an extension of standard answer set programs with consistency restoring rules and LPOD-like ordered disjunction. We present reductions of each of these languages into the standard ASP language, which gives us an alternative way to understand the extensions in terms of the standard ASP language.